Design of Telecom Operators' Network Data Sharing Platform Based on Hadoop+MPP Architecture - Huang Xin; Xinghui Yi; Zhenyu Chen (Dianxin kexue)
Based on using distributed computing and distributed storage technology, the telecom operators' network data sharing platform based on Hadoop +MPP architectures was studied. By integrating various distributed network management data, the network basic data platform, application platform and unified control platform were built.